2019
DOI: 10.1002/smll.201805416
|View full text |Cite
|
Sign up to set email alerts
|

Progress toward Understanding the Interactions between DNA Nanostructures and the Cell

Abstract: Advances in DNA nanotechnology empower the programmable assembly of DNA building blocks (oligonucleotides and plasmids) into DNA nanostructures with precise architectural control. As DNA nanostructures are biocompatible and can naturally enter mammalian cells without the aid of transfection agents, they have found numerous biological or biomedical applications as delivery carriers of therapeutic and imaging cargoes into mammalian cells for at least a decade. Nevertheless, mechanistic studies on how DNA nanostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 98 publications
0
18
1
Order By: Relevance
“…In addition, some aptamers can be added to other vertices of the tFNA, enabling complex identification of specific proteins on the cytomembrane, thereby improving the specificity of targeting. [36] However, several in vivo studies have indicated that DNA nanostructures produced by origami methods [37] are easily denatured and digested in a physiological environment. [38] The tFNA nanorobotics also faces this problem because most tFNA, which have not been specially modified, are absorbed by the kidney and liver and then metabolically eliminated, after injection through the tail vein to reach the target organ.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some aptamers can be added to other vertices of the tFNA, enabling complex identification of specific proteins on the cytomembrane, thereby improving the specificity of targeting. [36] However, several in vivo studies have indicated that DNA nanostructures produced by origami methods [37] are easily denatured and digested in a physiological environment. [38] The tFNA nanorobotics also faces this problem because most tFNA, which have not been specially modified, are absorbed by the kidney and liver and then metabolically eliminated, after injection through the tail vein to reach the target organ.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy may be utilized as a generic approach to explore cellular processes of DNA nanostructures for biomedical applications, especially for small structures which are supposed to bind to protein domains favorably than large ones. [23] Furthermore, it may be applicable to other nanomaterials, such as liposomes and inorganic nanoparticles, [24] with caution for mass spectrometry measurements. [25] We envision this proteomic exploration strategy can provide a strong supplement for fluorescence tracing methods utilized in exploration of cellular process of nanomaterials.…”
Section: Discussionmentioning
confidence: 99%
“…In this perspective, we call for in‐depth studies on the interactions between NPs and plant cells, because rational design of NP‐based transformation tools warrants fundamental understanding in the cellular uptake of gene nanocarriers. [ 36 ]…”
Section: Perspectivesmentioning
confidence: 99%